Evaluating the effects of recycled concrete aggregate size and concentration on properties of high-strength sustainable concrete - Md. Habibur Rahman, Sobuz; Datta, Shuvo Dip; Abu Sayed Mohammad, Akid; Vivian W.Y., Tam; Shoaib, Islam; Md. Jewel, Rana; Farhad, Aslani; Yalçınkaya, Çağlar; Norsuzailina, Mohamed Sutan (King Saud University, 2022)
This paper studies the fresh and mechanical properties of high-strength concrete (HSC) by incorporating recycled concrete aggregates (RCA) of varying sizes and concentrations. The recycled aggregate concrete (RAC) was prepared by partially replacing RCA with natural coarse aggregate (NCA) at 0%, 15%, 30%, and 45%, with aggregate sizes ranging from 5 to 12 and 12–20-mm. Fresh concrete properties, such as slump, Kelly ball, compacting factor, K-slump, and fresh density, were tested to determine the influence of RCA size and concentration. In addition, the mechanical properties were studied through the execution of compressive, split-tensile, and stress-strain tests. The test results revealed that increasing the RCA concentration declines the fresh and hardened properties of HSC. In the fresh concrete experimentation, the 12–20 mm aggregate size RAC mixes exhibited greater workability than the 5–12 mm aggregate mixes. On the contrary, 5–12 mm aggregate mixes RAC had higher compressive and split-tensile strength and a higher modulus of elasticity than 12–20 mm aggregate mixes concrete. When it comes to sustainability, the study found that the smaller size range of RAC produces inferior embodied CO2 (eCO2) and provides a cost-effective and sustainable solution for the construction industry.